Barriers and Opportunities to Employment for Persons with Disabilities in the Russian Federation - Kolybashkina, Nina (World Bank, Washington, DC, 2021)
The goal of this assessment is to identify barriers and opportunities to the supply of and demand for labor among persons with disabilities in Russia, as well as opportunities to increase their participation in the labor market. The research includes an overview of legis-lation, social policies, and national programs; an analysis of qualitative data, including the results of expert interviews and focus group discussions; and an analysis of quantitative data, including administrative information from the Ministry of Labor and Social Protection (MoLSP) and the Pension Fund of the Russian Federation (PFR) and a household survey conducted by the Russian State Statistical Service (Rosstat). A concerted effort was made to include and amplify the voices of persons with disabilities and the organizations that represent their interests. An assessment was undertaken of social protection and policy measures to facilitate the demand for and stimulate the supply of labor among persons with disabilities.